MiR‐208b regulates cell cycle and promotes skeletal muscle cell proliferation by targeting CDKN1A. Issue 4 (14th October 2018) - Wang, Jian; Song, Chengchuang; Cao, Xiukai; Li, Hui; Cai, Hanfang; Ma, Yilei; Huang, Yongzhen; Lan, Xianyong; Lei, Chuzhao; Ma, Yun; Bai, Yueyu; Lin, Fengpeng; et al.
Abstract: Skeletal muscle is the most abundant tissue in the body. The development of skeletal muscle cell is complex and affected by many factors. A sea of microRNAs (miRNAs) have been identified as critical regulators of myogenesis. MiR‐208b, a muscle‐specific miRNA, was reported to have a connection with fiber type determination. However, whether miR‐208b has effect on proliferation of muscle cell was under ascertained. In our study, cyclin‐dependent kinase inhibitor 1A ( CDKN1A ), which participates in cell cycle regulation, was predicted and then validated as one target gene of miR‐208b. We found that overexpression of miR‐208b increased the expression of cyclin D1, cyclin E1, and cyclin‐dependent kinase 2 at the levels of messenger RNA and protein in cattle primary myoblasts in vivo and in vitro. Flow cytometry showed that forced expression of miR‐208b increased the percentage of cells at the S phase and decreased the percentage of cells at the G0/G1 phase. These results indicated that miR‐208b participates in the cell cycle regulation of cattle primary myoblast cells. 5‐Ethynyl‐20‐deoxyuridine and 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assays showed that overexpression of miR‐208b promoted the proliferation of cattle primary myoblasts. Therefore, we conclude that miR‐208b participates in the cell cycle and proliferation regulation of cattle primary skeletal muscle cell through the posttranscriptional downregulation of CDKN1A . Abstract : Our data demonstrated that cyclin‐dependent kinase inhibitor 1A (CDKN1A) is a target gene of microRNA (miR)‐208b. MiR‐208b participates in the cell cycle and proliferation regulation of cattle primary skeletal muscle cell through the posttranscriptional downregulation of CDKN1A.